2020
DOI: 10.1186/s40560-020-00475-y
|View full text |Cite
|
Sign up to set email alerts
|

Operationalization of critical care triage during a pandemic surge using protocolized communication and integrated supportive care

Abstract: Triage becomes necessary when demand for intensive care unit (ICU) resources exceeds supply. Without triage, there is a risk that patients will be admitted to the ICU in the sequence that they present, disadvantaging those who either present later or have poorer access to healthcare. Moreover, if the patients with the best prognosis are not allocated life support, there is the possibility that overall mortality will increase. Before formulating criteria, principles such as maximizing lives saved and fairness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Furthermore, emotions and compassion should be verbalized more strongly, since the non-verbal part of communication is partially or completely omitted by the (video)telephony [ 18 , 19 ]. The implementation and realization of clear communication concepts is also important in connection with prioritization decisions and to avoid overtherapy [ 19 , 20 ]. If scarce resources lead to prioritize decisions, a feeling of withholding care can arise, which can only be circumvented through comprehensible communication, for example, according to the "SHARE talking map" (specifically to explain resource allocation), as illustrated in Table 4 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, emotions and compassion should be verbalized more strongly, since the non-verbal part of communication is partially or completely omitted by the (video)telephony [ 18 , 19 ]. The implementation and realization of clear communication concepts is also important in connection with prioritization decisions and to avoid overtherapy [ 19 , 20 ]. If scarce resources lead to prioritize decisions, a feeling of withholding care can arise, which can only be circumvented through comprehensible communication, for example, according to the "SHARE talking map" (specifically to explain resource allocation), as illustrated in Table 4 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, emotions and compassion should be verbalized more strongly, since the non-verbal part of communication is partially or completely omitted by the (video)telephony [17,18]. The implementation and realization of clear communication concepts is also important in connection with prioritization decisions and to avoid overtherapy [18,19]. If scarce resources lead to prioritization decisions, a feeling of withholding of care can arise, which can only be circumvented through comprehensible communication, for example, according to the "SHARE talking map" (speci cally to explain resource allocation), as illustrated in Table 4 [20].…”
Section: Communication With Relativesmentioning
confidence: 99%
“…The ignorance of users' views and their participation in designing such information systems has led to their lack of interest in such systems. 35,36 Therefore, the present study focused on the identification of the information needs and requirements of such a system from the users' point of view. Based on the study results, several methods were used to identify and extract indicators and requirements of the dashboard system which included investigation of similar information systems, user interviews, and questionnaires.…”
Section: Variables Based On Eucs Model 29 Research Variables Averagementioning
confidence: 99%
“…Therefore, patient triage is critical in situations like this since there is always a risk that patients may not be properly admitted to the ICU which may cause more harm and injury to the patients. 35 Regarding the fact that the triage, emergency, and ICU departments are involved in the process of providing health care services to COVID-19 patients, it is important to monitor the workflow of these units. Accordingly, the indicators required for COVID-19 management in the present study were identified through the assessment of the information needs of dashboard users.…”
Section: Variables Based On Eucs Model 29 Research Variables Averagementioning
confidence: 99%